PENGARUH ORGANIC SOIL TREATMENT (OST) DAN SELANG WAKTU APLIKASI LARUTAN LANDETO TERHADAP HASIL BAWANG MERAH PADA REGOSOL - Settings Jeanne I Nendissa; Nonce Wattimena (Jurnal Matematika Sains dan Teknologi, 2009)
This research was intended to determine the rate of Organic Soil Treatment (OST) and the interval of application of Landeto solution or their interaction on the growth of shallots grown in the regosol soil. This research was conducted in the green house of Departement of Soil Science, Faculty of Agriculture Gadjah Mada University. A Randomized Complete Block Design, employing a factorial treatment was chosen. The first factors was rates of OST, i.e,: 0, 3, 6, 9 and 12 ton ha?. The second factors was interval of application of Landeto Solution, i.e, : 3, 5 and 7 days. The combination treatments were repeated 3 times. Results of the research showed that; 1) Intermedien between rates of OST at 6 ton ha? and interval of application of Landeto solution ot 5 days, was found in bulb number per hills ( 29.87, cm2 ) respectively. 2) Application of OST, at 6 ton ha? had a significant effect on the plant fresh weight and the fresh bulb weigth, 3) Application of Landeto solution at different intervals had no significant effect on all components and crop yield.